(3GdWQGR aj TQM VHW GdNQGRs - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf YHO GdLdjd GdJfjSjs ((3YHO GdcQje Hf eMeO Hf YHO GdcQje Hf ROGe Gdjefi s)
(3ChdgG (B:s
(3jHOC HGdbhd ai CMcGe hVY GdMQcI s
(3BNQgG (B:s
(3jfJgi HUM eG jLYd HGdMeQGA cGdMQcGJ hZjQgG s
(3HgG fXGe GdJYbjHIs
(3VHW GdNQGR efXheI ai QSe GdNWs
(3HChdgG agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GddZIs